Profil Hidrasi Kulit dan Kerusakan Kulit Akibat Matahari pada Remaja di Panti Asuhan Pondok Kasih Agape - Melani Rakhmi Mantu; Giovanno Sebastian Yogie; William Gilbert Satyanagara; Sukmawati Tansil Tan; Catharina Sagita Moniaga (Journal of Educational Innovation and Public Health, 2023)
Healthy skin is necessary for the body to provide active protection against changes in the environment. In order to preserve skin moisture and give protection from ultraviolet (UV) light, a healthy stratum corneum is mandatory. Several skin disease, including atopic dermatitis, contact dermatitis, ichthiosis, and psoriasis, are associated with anomalies in stratum corneum hydration. Meanwhile, erythema, photosensitivity, and skin cancer can all result from prolonged exposure to UV radiation. This study were done withis a cross sectional with non-random consecutive sampling. The parameters taken in this study include demographic (age and gender), skin moisture / moist (%) and sun damage / UV Damage (%). Thirty adolescents between 12-18 years were included in the study (20 male (66,7%), vs 10 female (33,3%). The mean facial moisture was 63.6 (± 14.72)%, and sun damage was 31.53 (±14.47)%. These data suggest that dry skin and UV skin damage can happen to anyone including teenagers. Therefore it is essential to maintain the skin moisture and protect it from UV radiation, to obtain healthy skin and prevent associated skin problems.